Investigation of ABS–oil palm fiber (Elaeis guineensis) composites filament as feedstock for fused deposition modeling - Ahmad, Mohd Nazri; Ishak, Mohamad Ridzwan; Mohammad Taha, Mastura; Mustapha, Faizal; Leman, Zulkiflle (Emerald Group Publishing Ltd., 2023)
The purpose of this paper is to investigate the tensile strength, Young’s modulus, dimensional stability and porosity of acrylonitrile butadiene styrene (ABS)–oil palm fiber composite filament for fused deposition modeling (FDM). Design/methodology/approach: A new feedstock material for FDM comprising oil palm fiber and ABS as a matrix was developed by a twin screw extruder. The composite filament contains 0, 3, 5 and 7 Wt. of oil palm fiber in the ABS matrix. The tensile test is then performed on the fiber composite filament, and the wire diameter is measured. In this study, the Archimedes method was used to determine the density and the porosity of the filament. The outer surface of the wire composite was examined using an optical microscope, and the analysis of variance was used to assess the significance and the relative relevance of the primary factor. Findings: The results showed that increasing the fiber loading from 0.15 to 0.4 MPa enhanced tensile strength by 60. Then, from 16.1 to 18.3 MPa, the Young’s modulus rose by 22.8. The density of extruded filament decreased and the percentage of porosity increased when the fiber loading was increased from 3 to 7 Wt.. The diameter deviation of the extruded filaments varied from −0.21 to 0.04 mm. Originality/value: This paper highlights a novel natural resource-based feedstock material for FDM. Its mechanical and physical properties were also discovered.